Farmers perceptions and adoption of new agricultural technology: analysis of modern mangrove rice varieties in Guinea Bissau - Adesina, A.; Seidi, S. (1995)
This paper examines the diffusion and adoption of improved mangrove swamp rice varieties (MV's) in Guinea Bissau, using evidence from the Cumbidja River Basin, a major mangrove rice growing area of the country. The results of the study show that the adoption of MV's has been rapid and impressive in the Cumbidja zone. Diffusion of the MV's which started in 1983 with 13% of farmers, had reached 70% of farmers by 1993. A Logit model was used to quantify the factors that determine the observed adoption patterns. While contact with extension or rice development projects has positively influenced farmers' adoption, it is farmers' assessments of the superiority of these MV's to local varieties (for some key technology attributes) that has principally motivated farmers' adoption of the MV's. Farmers' perceptions and adoption of new agricultural technology: analysis of modern mangrove rice varieties in Guinea Bissau. Available from: